PENGARUH SINERGI, KREDIBILITAS, KEPEMILIKAN BARU, BUDAYA DAN TATA KELOLA PERUSAHAAN TERHADAP KINERJA BANK PASCA PRIVATISASI DI INDONESIA. - Hadiyanto Budisetio (Media Riset Akuntansi, Auditing & Informasi, 2006)
The purpose of this research is to address and learn more about privatization, especially in the banking industry in Indonesia. This research will be seen purely from the academic point of views which definitely involving many aspects of the theories that have been developed by expert from overseas and local as well. The focus of this study is to identify the impact of several important variables such as synergy, credibility, new ownership, culture and good corporate governance to the bank performance after privatized. Those five variables are believed to be the critical aspects in the merger and acquisition process. In order to support this research we have developed a simple research model. This model could help simplify the way of thinking and make better framework for the research. A simple questionnaire has also been developed in order to collect the primary data from target respondents, even though the depth of the questionnaire was not proven yet. Respondents who participate in this research are coming from privatized banks, either the bank was privatized through Initial Public Offering or through strategic partner. There were 188 data collected from more than 300 questionnaires distributed to bank officers at the head office of privatized banks in Indonesia. All variables used in this research can not be measured directly. Therefore, to be more accurate, it was done through some of indicators. Sequential Equation Modeling has been chosen as the research methodology and Lisrel 8.30 and SPSS 13.0 has also been chosen as the statistic software to be used.As a result of this research, only two hypotheses can be confirmed and the other nine hypotheses can not be confirmed. These results definitely do not match with the previous research conducted by researchers from other countries, but it could be used to broaden our way of thinking whereby other situation and condition could really produce different result.Keywords: Privatization, Questionaire, Sequential Equation Modeling